2011
DOI: 10.1118/1.3562896
|View full text |Cite
|
Sign up to set email alerts
|

Spectral method for the correction of the Cerenkov light effect in plastic scintillation detectors: A comparison study of calibration procedures and validation in Cerenkov light‐dominated situations

Abstract: The authors conclude that the spectral method can be used to accurately correct the Cerenkov light effect in PSDs. The authors confirmed the importance of maximizing the difference of Cerenkov light production between calibration measurements. The authors also found that the attenuation of the optical fiber, which is assumed to be constant in the original formulation of the spectral method, may cause a variation of the calibration factors in some experimental setups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
161
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(165 citation statements)
references
References 26 publications
(35 reference statements)
3
161
1
Order By: Relevance
“…[21][22][23][24] The main drawback of plastic scintillators is represented by the generation ofČerenkov light in the optical fibre guide when the scintillator is exposed to a radiation field. Two main approaches have been suggested to subtract thě Cerenkov light component: the method proposed by Beddar et al, 15,16 which uses a background optical fibre not coupled with a scintillating fibre, and the two-fibre or spectral method, proposed by Fontbonne et al 25 and reformulated by Guillot et al, 26 which is based on the dependence of the intensity of thě Cerenkov light on the length of the exposed fibre and measures the light signal by means of two different wavelength channels. Morin 22 has proposed a modification of the measurement procedure proposed by Guillot et al 26 to determine the Cerenkov spectrum with the detector placed with the stem parallel to the beam axis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23][24] The main drawback of plastic scintillators is represented by the generation ofČerenkov light in the optical fibre guide when the scintillator is exposed to a radiation field. Two main approaches have been suggested to subtract thě Cerenkov light component: the method proposed by Beddar et al, 15,16 which uses a background optical fibre not coupled with a scintillating fibre, and the two-fibre or spectral method, proposed by Fontbonne et al 25 and reformulated by Guillot et al, 26 which is based on the dependence of the intensity of thě Cerenkov light on the length of the exposed fibre and measures the light signal by means of two different wavelength channels. Morin 22 has proposed a modification of the measurement procedure proposed by Guillot et al 26 to determine the Cerenkov spectrum with the detector placed with the stem parallel to the beam axis.…”
Section: Introductionmentioning
confidence: 99%
“…Two main approaches have been suggested to subtract thě Cerenkov light component: the method proposed by Beddar et al, 15,16 which uses a background optical fibre not coupled with a scintillating fibre, and the two-fibre or spectral method, proposed by Fontbonne et al 25 and reformulated by Guillot et al, 26 which is based on the dependence of the intensity of thě Cerenkov light on the length of the exposed fibre and measures the light signal by means of two different wavelength channels. Morin 22 has proposed a modification of the measurement procedure proposed by Guillot et al 26 to determine the Cerenkov spectrum with the detector placed with the stem parallel to the beam axis. Considering that the Beddar et al's approach depends on fibre, coupling and photodetector equivalence, the Guillot et al method seems to be more appropriate, reducing thě Cerenkov effect within 0.7%, which represents an acceptable uncertainty for the aims of radiation therapy dosimetry.…”
Section: Introductionmentioning
confidence: 99%
“…The system was calibrated for Cerenkov radiation by evaluating the different scintillating light outputs in 40×40.2emcm2, with maximum versus minimum length of optic fibers in field. The dual‐channel method (29) derives the gain and Cerenkov light ratio (CLR) as below: (30) CLR=SC1italicmax40SC1italicmin40SC2italicmax40SC2italicmin40 Gain=1false(SC1italicmin40SC2italicmin40×CLRfalse) …”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that by monitoring the light under two different wavelength filters, it is possible to isolate the luminescence signal from the Cherenkov signal. [79][80][81][82] As a consequence of the large amount of research into this area, it is now widely considered that the issue of the stem effect has been addressed and no longer poses a limitation in the sensors' potential for radiotherapy dosimetry.…”
mentioning
confidence: 99%
“…A number of techniques are proposed for removing the stem effect in optical fibre-based dosemeters, such as using a dual reference fibre, [74][75][76][77] optical filtering 72 and a temporal approach, where the measurement reading is timed such that the stem effect has decayed out. 78 One of the most favoured methods of stem removal is the spectral, or chromatic, method 73,79,80 developed by Fontbonne et al 81 The technique exploits the difference in optical spectra of the luminescence signal and Cherenkov radiation. It has been shown that by monitoring the light under two different wavelength filters, it is possible to isolate the luminescence signal from the Cherenkov signal.…”
mentioning
confidence: 99%